The Effect of Liquidity, Profitability and Asset Growth on the Dividend Payout Ratio in Transportation Sector Companies Listed on The Indonesian Stock Ex-change (Idx) For the Year 2017-2019 - Heliani; Eneng Rina; Mia Safitri Rahayu; Muhammad Rizky Ramdaniansyah (Nusantara Science and Technology Proceedings, 2020)
Transportation is an effort to move objects from one area to another. Investment in a company is an important thing to operate its business activities. Investors expect to receive dividends when investing. The dividend policy of transportation companies in the last few years poses a significant risk of problems. This study aims to prove the effect of liquidity (current ratio), profitability, and asset growth against the DPR. This research is of a quantitative type, using a population of 41 transportation sector industries listed on the Indonesia Stock Exchange 2017-2019. Sampling was filtered using the purposive sampling method. 8 industries meet the criteria. Data analysis and hypothesis testing using classical assumption test, multiple linear regression analysis, t-test, and coefficient of determination. This study succeeded in revealing that liquidity and profitability did not affect the dividend payout ratio, while asset growth affected the DPR.